Method for improving residual strength of lithium aluminosilicate glass after damage
By combining a series of heat treatments and molten salt strengthening treatments, the problem of insufficient strength of lithium aluminum silicate glass after damage was solved, achieving a significant increase in strength and a guarantee of safety.
Patent Information
- Application Number
- CN202411362568.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-07
AI Technical Summary
Existing technologies cannot effectively improve the residual strength of lithium aluminum silicate glass after damage, resulting in a significant reduction in strength when the damage depth exceeds the stress layer depth, which affects the safety of use.
By combining a series of heat treatments, molten salt strengthening and thermal shock treatments, including a first preheating treatment, a first molten salt strengthening treatment, a first annealing treatment, a second preheating treatment, a second molten salt strengthening treatment, a second annealing treatment, a first heat treatment, a third preheating treatment, a third molten salt strengthening treatment, a third annealing treatment, thermal shock treatment and corrosion treatment, the residual strength of lithium aluminosilicate glass after damage is significantly improved.
It significantly improves the residual strength of lithium aluminum silicate glass after damage, is simple to operate, and provides a significant strength improvement, ensuring the safety of glass use.
Smart Images

Figure BDA0005065307040000101 
Figure BDA0005065307040000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass processing, and in particular relates to a method for improving the residual strength of lithium aluminum silicate glass after damage. Background Art
[0002] Glass materials have excellent physical properties such as high strength, high hardness, good optical properties, and the ability to be used stably at high temperatures. Therefore, they are widely used in civil and defense military fields such as aircraft and automobile windshields, armor protection, etc. Among them, lithium aluminum silicate glass can be chemically strengthened by two ion exchanges of Li-Na and Na-K. After strengthening, the stress layer depth can reach more than 200μm. After the surface is slightly damaged less than the stress layer depth, it still has a high residual strength to ensure the short-term safety of the glass. However, when the damage depth is greater than the stress layer depth, the inhibitory effect of the surface compressive stress on crack growth disappears, and stress concentration will occur at the crack tip, which promotes crack growth under the action of central tensile stress, greatly reducing the strength of lithium aluminum silicate glass and reducing the safety of its product use. Therefore, after the glass is damaged, it needs to be strengthened to improve its strength to ensure its safety in use.
[0003] Existing methods for improving glass strength are mostly achieved through chemical strengthening or physical strengthening, but these two methods are not very effective in improving the residual strength of lithium aluminum silicate glass after damage.
[0004] To this end, the present invention is proposed. Summary of the invention
[0005] The main purpose of the present invention is to provide a method for improving the residual strength of lithium aluminum silicate glass after damage. The method of the present invention can significantly improve the residual strength of lithium aluminum silicate glass after damage and is simple to operate.
[0006] In order to achieve the above objectives, the present invention provides the following technical solutions.
[0007] The present invention provides a method for improving the residual strength of lithium aluminosilicate glass after damage. The method comprises the following steps: sequentially performing a first preheating treatment, a first molten salt strengthening treatment, a first annealing treatment, a second preheating treatment, a second molten salt strengthening treatment, a second annealing treatment, a first heat treatment, a third preheating treatment, a third molten salt strengthening treatment, a third annealing treatment, a cold and hot shock treatment, a second heat treatment, and a corrosion treatment on the lithium aluminosilicate glass with surface damage to obtain a target lithium aluminosilicate glass; the thickness of the lithium aluminosilicate glass is 2 mm to 10 mm.
[0008] In some embodiments of the present invention, the damage depth of the surface damage is ≤0.5 mm and is not 0.
[0009] In some embodiments of the present invention, the surface damage includes at least one of scratches, erosion, and bumps.
[0010] In some embodiments of the present invention, the first preheat treatment, the second preheat treatment and the third preheat treatment each independently include: heating the lithium aluminum silicate glass from room temperature to 340°C to 380°C at a heating rate of 1°C / min to 3°C / min, and keeping the temperature for 1h to 3h.
[0011] In some embodiments of the present invention, the temperature of the first molten salt strengthening treatment is 380°C to 450°C, and the time is 3h to 24h; and / or, the temperature of the second molten salt strengthening treatment is 380°C to 450°C, and the time is 0.5h to 5h; and / or, the temperature of the third molten salt strengthening treatment is 380°C to 450°C, and the time is 0.5h to 3h.
[0012] In some embodiments of the present invention, the first molten salt strengthening treatment, the second molten salt strengthening treatment, and the third molten salt strengthening treatment each independently use a mixed molten salt comprising potassium nitrate, sodium nitrate, and calcium fluoride, and the mass percentage of potassium nitrate and sodium nitrate in the mixed molten salt used in the first molten salt strengthening treatment is different from the mass percentage of potassium nitrate and sodium nitrate in the mixed molten salt used in the second molten salt strengthening treatment and the third molten salt strengthening treatment.
[0013] In some embodiments of the present invention, in the mixed molten salt used in the first molten salt strengthening treatment, the mass percentage of sodium nitrate is 65% to 85%, the mass percentage of calcium fluoride is 0.5%, and the balance is sodium nitrate.
[0014] In some embodiments of the present invention, in the mixed molten salt used in the second molten salt strengthening treatment and the third molten salt strengthening treatment, the mass percentage of potassium nitrate is 80% to 90%, the mass percentage of calcium fluoride is 0.5%, and the balance is sodium nitrate.
[0015] In some embodiments of the present invention, the first annealing treatment, the second annealing treatment and the third annealing treatment each independently include: cooling the lithium aluminum silicate glass after molten salt strengthening treatment to room temperature at a cooling rate of 1°C / min to 3°C / min.
[0016] In some embodiments of the present invention, the first heat treatment comprises: heating the lithium aluminum silicate glass from room temperature to 380°C to 450°C at a heating rate of 1°C / min to 3°C / min under vacuum or oxygen atmosphere, and keeping the temperature for 2h to 4h.
[0017] In some embodiments of the present invention, the second heat treatment comprises: heating the lithium aluminum silicate glass from room temperature to 80°C to 100°C at a heating rate of 1°C / min to 3°C / min under vacuum or oxygen atmosphere, and keeping the temperature for 96h to 120h.
[0018] In some embodiments of the present invention, the thermal shock treatment comprises: subjecting the lithium aluminum silicate glass to thermal shocks for 5 to 10 times, each thermal shock temperature being 70° C. and each cold shock temperature being -40° C.
[0019] In some embodiments of the present invention, the corrosion treatment includes: performing corrosion treatment on the damaged surface of the lithium aluminum silicate glass, and the corrosion time is 1 min to 2 min.
[0020] In some embodiments of the present invention, the etching solution used in the etching treatment contains potassium hydroxide.
[0021] Compared with the prior art, the present invention achieves the following technical effects:
[0022] The method of the present invention can significantly improve the residual strength of damaged lithium aluminum silicate glass, is simple to operate, and significantly improves the strength.
[0023] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. DETAILED DESCRIPTION
[0024] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.
[0026] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0027] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0028] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.
[0029] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0030] In view of the fact that the existing methods for improving glass strength are not effective in improving the residual strength of lithium aluminosilicate glass after damage, the present invention provides a method for improving the residual strength of lithium aluminosilicate glass after damage. The key lies in sequentially subjecting lithium aluminosilicate glass with a thickness of 2 mm to 10 mm and surface damage to a first preheating treatment, a first molten salt strengthening treatment, a first annealing treatment, a second preheating treatment, a second molten salt strengthening treatment, a second annealing treatment, a first heat treatment, a third preheating treatment, a third molten salt strengthening treatment, a third annealing treatment, a cold and hot shock treatment, a second heat treatment, and a corrosion treatment to obtain a target lithium aluminosilicate glass, thereby achieving the improvement of the residual strength of the lithium aluminosilicate glass after damage.
[0031] In the embodiment of the present invention, room temperature refers to a temperature in the range of 10°C to 30°C, for example, it can be 10°C, 15°C, 20°C, 25°C, 30°C or any value satisfying the above range.
[0032] (1) First preheating treatment.
[0033] In an embodiment of the present invention, the lithium aluminum silicate glass with surface damage is heated from room temperature to 340° C. to 380° C. at a heating rate of 1° C. / min to 3° C. / min and kept at this temperature for 1 h to 3 h.
[0034] In some embodiments of the present invention, the temperature of the first preheat treatment may be one of 340° C., 350° C., 360° C., 370° C., 380° C. or any value within the above range.
[0035] In some embodiments of the present invention, the time of the first preheating treatment may be one of 1 h, 2 h, 3 h, or any value within the above range.
[0036] In some embodiments of the present invention, the heating rate of the first preheating treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value within the above range.
[0037] In some embodiments of the present invention, the surface damage may be scratches, erosion, bumps, and the like.
[0038] In some embodiments of the present invention, the damage depth of the surface damage is ≤0.5 mm and is not 0. For example, the damage depth can be one of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm or any value satisfying the above range.
[0039] (2) First molten salt strengthening treatment.
[0040] In an embodiment of the present invention, the lithium aluminosilicate glass preheated in step (1) is immersed in a first molten salt for strengthening treatment, thereby improving the strength of the lithium aluminosilicate glass.
[0041] In some embodiments of the present invention, the temperature of the first molten salt strengthening treatment is 380°C to 450°C. Exemplarily, the temperature of the first molten salt strengthening treatment can be one of 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or any value satisfying the above range.
[0042] In some embodiments of the present invention, the time for the first molten salt strengthening treatment is 3 h to 24 h. Exemplarily, the time for the first molten salt strengthening treatment can be one of 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h or any value that satisfies the above range.
[0043] In some embodiments of the present invention, the first molten salt strengthening treatment uses a mixed molten salt containing potassium nitrate, sodium nitrate, and calcium fluoride.
[0044] In some embodiments of the present invention, in the mixed molten salt used in the first molten salt strengthening treatment, the mass percentage of sodium nitrate is 65% to 85%, the mass percentage of calcium fluoride is 0.5%, and the balance is sodium nitrate.
[0045] Exemplarily, the mass percentage of sodium nitrate in the mixed molten salt used in the first molten salt strengthening treatment can be one of 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85% or any value that meets the above range.
[0046] (3) First annealing treatment.
[0047] In an embodiment of the present invention, the lithium aluminum silicate glass after the first molten salt strengthening treatment in step (2) is cooled to room temperature at a cooling rate of 1° C. / min to 3° C. / min.
[0048] In some embodiments of the present invention, the cooling rate of the first annealing treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value satisfying the above range.
[0049] (4) Second preheating treatment.
[0050] In an embodiment of the present invention, the lithium aluminum silicate glass after the first annealing treatment in step (3) is heated from room temperature to 340° C. to 380° C. at a heating rate of 1° C. / min to 3° C. / min and kept at this temperature for 1 h to 3 h.
[0051] In some embodiments of the present invention, the temperature of the second preheat treatment may be one of 340° C., 350° C., 360° C., 370° C., 380° C. or any value satisfying the above range.
[0052] In some embodiments of the present invention, the time of the second preheating treatment may be one of 1 h, 2 h, 3 h, or any value within the above range.
[0053] In some embodiments of the present invention, the heating rate of the second preheating treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value within the above range.
[0054] (5) Second molten salt strengthening treatment.
[0055] In an embodiment of the present invention, the lithium aluminosilicate glass preheated in step (4) is immersed in a mixed molten salt for strengthening treatment, thereby improving the strength of the lithium aluminosilicate glass.
[0056] In some embodiments of the present invention, the temperature of the second molten salt strengthening treatment is 380°C to 450°C. Exemplarily, the temperature of the second molten salt strengthening treatment can be one of 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or any value satisfying the above range.
[0057] In some embodiments of the present invention, the time of the second molten salt strengthening treatment is 0.5h to 5h. Exemplarily, the time of the second molten salt strengthening treatment can be one of 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h, 4.5h, 5h or any value that satisfies the above range.
[0058] In some embodiments of the present invention, the second molten salt strengthening treatment uses a mixed molten salt containing potassium nitrate, sodium nitrate, and calcium fluoride.
[0059] In some embodiments of the present invention, in the mixed molten salt used in the second molten salt strengthening treatment, the mass percentage of potassium nitrate is 80% to 90%, the mass percentage of calcium fluoride is 0.5%, and the balance is sodium nitrate.
[0060] Illustratively, the mass percentage of potassium nitrate in the mixed molten salt used in the second molten salt strengthening treatment can be one of 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or any value that meets the above range.
[0061] (6) Second annealing treatment.
[0062] In an embodiment of the present invention, the lithium aluminum silicate glass after the second molten salt strengthening treatment in step (5) is cooled to room temperature at a cooling rate of 1° C. / min to 3° C. / min.
[0063] In some embodiments of the present invention, the cooling rate of the second annealing treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value satisfying the above range.
[0064] (7) First heat treatment.
[0065] In an embodiment of the present invention, under vacuum or oxygen atmosphere conditions, the lithium aluminum silicate glass annealed in step (6) is heated from room temperature to 380°C to 450°C at a heating rate of 1°C / min to 3°C / min, and kept warm for 2h to 4h, thereby eliminating the internal stress of the lithium aluminum silicate glass.
[0066] In some embodiments of the present invention, the temperature of the first heat treatment can be one of 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or any value satisfying the above range.
[0067] In some embodiments of the present invention, the time of the first heat treatment may be one of 2 h, 3 h, 4 h or any value satisfying the above range.
[0068] In some embodiments of the present invention, the heating rate of the first heat treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value satisfying the above range.
[0069] (8) Third preheating treatment.
[0070] In an embodiment of the present invention, the lithium aluminum silicate glass after the first heat treatment in step (7) is heated from room temperature to 340°C to 380°C at a heating rate of 1°C / min to 3°C / min and kept at this temperature for 1h to 3h.
[0071] In some embodiments of the present invention, the temperature of the third preheat treatment may be one of 340° C., 350° C., 360° C., 370° C., 380° C. or any value satisfying the above range.
[0072] In some embodiments of the present invention, the time of the third preheating treatment may be one of 1 h, 2 h, 3 h, or any value within the above range.
[0073] In some embodiments of the present invention, the heating rate of the third preheating treatment may be one of 1°C / min, 2°C / min, 3°C / min, or any value within the above range. (9) Third molten salt strengthening treatment.
[0074] (9) The third molten salt strengthening treatment.
[0075] In an embodiment of the present invention, the lithium aluminosilicate glass after the third preheating treatment in step (8) is immersed in a mixed molten salt for strengthening treatment, thereby achieving the improvement of the strength of the lithium aluminosilicate glass.
[0076] In some embodiments of the present invention, the temperature of the third molten salt strengthening treatment is 380°C to 450°C. Exemplarily, the temperature of the third molten salt strengthening treatment can be one of 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or any value satisfying the above range.
[0077] In some embodiments of the present invention, the time of the third molten salt strengthening treatment is 0.5h to 3h. Exemplarily, the time of the third molten salt strengthening treatment can be one of 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h or any value that satisfies the above range.
[0078] In some embodiments of the present invention, the third molten salt strengthening treatment uses a mixed molten salt containing potassium nitrate, sodium nitrate, and calcium fluoride.
[0079] In some embodiments of the present invention, in the mixed molten salt used in the third molten salt strengthening treatment, the mass percentage of potassium nitrate is 80% to 90%, the mass percentage of calcium fluoride is 0.5%, and the balance is sodium nitrate.
[0080] Illustratively, the mass percentage of potassium nitrate in the mixed molten salt used in the third molten salt strengthening treatment can be one of 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or any value that meets the above range.
[0081] (10) Third annealing treatment.
[0082] In an embodiment of the present invention, the lithium aluminum silicate glass after the third molten salt strengthening treatment in step (9) is cooled to room temperature at a cooling rate of 1° C. / min to 3° C. / min.
[0083] In some embodiments of the present invention, the cooling rate of the third annealing treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value satisfying the above range.
[0084] (11) Hot and cold shock treatment.
[0085] In an embodiment of the present invention, the lithium aluminum silicate glass after the third annealing treatment in step (10) is subjected to hot and cold shocks 5 to 10 times, each time at a hot shock temperature of 70° C. and each time at a cold shock temperature of -40° C.
[0086] (12) Second heat treatment.
[0087] In an embodiment of the present invention, under vacuum or oxygen atmosphere conditions, the lithium aluminum silicate glass after the cold and hot shock treatment in step (11) is heated from room temperature to 80°C to 100°C at a heating rate of 1°C / min to 3°C / min, and kept warm for 96h to 120h.
[0088] In some embodiments of the present invention, the temperature of the second heat treatment may be one of 80° C., 90° C., 100° C. or any value satisfying the above range.
[0089] In some embodiments of the present invention, the time of the second heat treatment can be one of 96h, 97h, 98h, 99h, 100h, 105h, 110h, 115h, 120h or any value that meets the above range.
[0090] In some embodiments of the present invention, the heating rate of the second heat treatment may be one of 1° C. / min, 2° C. / min, 3° C. / min, or any value satisfying the above range.
[0091] (13) Corrosion treatment.
[0092] In an embodiment of the present invention, the damaged surface of the lithium aluminum silicate glass after the second heat treatment in step (12) is subjected to corrosion treatment, and the corrosion time is 1 min to 2 min.
[0093] In some embodiments of the present invention, the corrosion time may be 1 min, 2 min, or any value satisfying the above range.
[0094] In some embodiments of the present invention, the etching solution used in the etching treatment may be potassium hydroxide, for example, potassium hydroxide is used to etch the damaged surface of the glass.
[0095] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0096] Example 1
[0097] Disclosed is a method for improving the residual strength of lithium aluminosilicate glass after damage. The method is for lithium aluminosilicate glass with surface damage, and is specifically prepared by sandblasting the surface of the lithium aluminosilicate glass original sheet with 0.069 MPa air pressure and 60 mesh gravel according to the relevant requirements of ASTM C158. The size of the lithium aluminosilicate glass original sheet is 250 mm×38 mm×3 mm.
[0098] The method for improving the residual strength of lithium aluminosilicate glass after damage in Example 1 comprises the following steps:
[0099] (1) Lithium aluminum silicate glass with surface damage was preheated in a furnace at a preheating temperature of 380°C and a heating rate of 3°C / min.
[0100] (2) The lithium aluminum silicate glass preheated in step (1) is immersed in a mixed molten salt (80% sodium nitrate + 19.5% potassium nitrate + 0.5% calcium fluoride) at a temperature of 420° C. for 3 hours.
[0101] (3) Cooling the lithium aluminum silicate glass after the molten salt strengthening treatment in step (2) to 25° C. in the furnace at a cooling rate of 3° C. / min.
[0102] (4) Preheating the lithium aluminum silicate glass annealed in step (3) by heating in a furnace, wherein the preheating temperature is 380° C. and the heating rate is 3° C. / min.
[0103] (5) The lithium aluminum silicate glass preheated in step (4) is immersed in a mixed molten salt (90% potassium nitrate + 9.5% sodium nitrate + 0.5% calcium fluoride) at a temperature of 420° C. for 1 hour.
[0104] (6) Cooling the lithium aluminum silicate glass after the molten salt strengthening treatment in step (5) to 25° C. in the furnace at a cooling rate of 3° C. / min.
[0105] (7) The lithium aluminum silicate glass annealed in step (6) is heat treated in a vacuum environment at a temperature of 400° C. The heat treatment time is 2 h and the heating rate is 3° C. / min.
[0106] (8) Preheating the lithium aluminum silicate glass after the heat treatment in step (7) by heating in a furnace, wherein the preheating temperature is 380° C. and the heating rate is 3° C. / min.
[0107] (9) The lithium aluminum silicate glass preheated in step (8) is immersed in a mixed molten salt (90% potassium nitrate + 9.5% sodium nitrate + 0.5% calcium fluoride) at a temperature of 420° C. for 2 hours.
[0108] (10) Cooling the lithium aluminum silicate glass after the molten salt strengthening treatment in step (9) to 25° C. in the furnace at a cooling rate of 3° C. / min.
[0109] (11) The lithium aluminum silicate glass annealed in step (10) is subjected to hot and cold shock for 7 times, each time at a hot shock temperature of 70° C. and each time at a cold shock temperature of −40° C.
[0110] (12) The lithium aluminum silicate glass subjected to the cold and hot shock treatment in step (11) is subjected to heat treatment in a vacuum environment at 100° C. The heat treatment time is 100 h and the heating rate is 3° C. / min.
[0111] (13) The damaged surface of the lithium aluminum silicate glass after the heat treatment in step (12) is corroded by potassium hydroxide for 1 minute.
[0112] The original lithium aluminosilicate glass sheet in Example 1 and the damaged lithium aluminosilicate glass obtained by the above-mentioned method were subjected to four-point bending tests according to the test method specified in ASTM C158. The test strength data are shown in Table 1.
[0113] Table 1 Summary of the strength of the original lithium aluminum silicate glass and the lithium aluminum silicate glass treated by the method in Example 1
[0114]
[0115] Example 2
[0116] A method for improving the residual strength of lithium aluminosilicate glass after damage is disclosed. The method is for lithium aluminosilicate glass with surface damage, and is specifically prepared by sandblasting the surface of the chemically strengthened lithium aluminosilicate glass with 60-mesh grit at 0.069 MPa pressure according to the relevant requirements of ASTM C158. The size of the chemically strengthened lithium aluminosilicate glass is 250 mm×38 mm×3 mm.
[0117] The method for improving the residual strength of lithium aluminosilicate glass after damage in Example 2 comprises the following steps:
[0118] (1) Lithium aluminum silicate glass with surface damage was preheated in a furnace at a preheating temperature of 380°C and a heating rate of 3°C / min.
[0119] (2) The lithium aluminum silicate glass preheated in step (1) is immersed in a mixed molten salt (80% sodium nitrate + 19.5% potassium nitrate + 0.5% calcium fluoride) at a temperature of 420° C. for 3 hours.
[0120] (3) Cooling the lithium aluminum silicate glass after the molten salt strengthening treatment in step (2) to 25° C. in the furnace at a cooling rate of 3° C. / min.
[0121] (4) Preheating the lithium aluminum silicate glass annealed in step (3) by heating in a furnace, wherein the preheating temperature is 380° C. and the heating rate is 3° C. / min.
[0122] (5) The lithium aluminum silicate glass preheated in step (4) is immersed in a mixed molten salt (90% potassium nitrate + 9.5% sodium nitrate + 0.5% calcium fluoride) at a temperature of 420° C. for 1 hour.
[0123] (6) Cooling the lithium aluminum silicate glass after the molten salt strengthening treatment in step (5) to 25° C. in the furnace at a cooling rate of 3° C. / min.
[0124] (7) The lithium aluminum silicate glass annealed in step (6) is heat treated in a vacuum environment at a temperature of 400° C. The heat treatment time is 2 h and the heating rate is 3° C. / min.
[0125] (8) Preheating the lithium aluminum silicate glass after the heat treatment in step (7) by heating in a furnace, wherein the preheating temperature is 380° C. and the heating rate is 3° C. / min.
[0126] (9) The lithium aluminum silicate glass preheated in step (8) is immersed in a mixed molten salt (90% potassium nitrate + 9.5% sodium nitrate + 0.5% calcium fluoride) at a temperature of 420° C. for 2 hours.
[0127] (10) Cooling the lithium aluminum silicate glass after the molten salt strengthening treatment in step (9) to 25° C. in the furnace at a cooling rate of 3° C. / min.
[0128] (11) The lithium aluminum silicate glass annealed in step (10) is subjected to hot and cold shock for 7 times, each time at a hot shock temperature of 70° C. and each time at a cold shock temperature of −40° C.
[0129] (12) The lithium aluminum silicate glass subjected to the cold and hot shock treatment in step (11) is subjected to heat treatment in a vacuum environment at 100° C. The heat treatment time is 100 h and the heating rate is 3° C. / min.
[0130] (13) The damaged surface of the lithium aluminum silicate glass after the heat treatment in step (12) is corroded by potassium hydroxide for 1 minute.
[0131] The chemically strengthened lithium aluminosilicate glass without damage treatment in Example 2 and the damaged chemically strengthened lithium aluminosilicate glass obtained by the above method were subjected to four-point bending tests according to the test method specified in ASTM C158. The test strength data are shown in Table 2.
[0132] Table 2 Summary of the strength of chemically strengthened lithium aluminosilicate glass in Example 2
[0133]
[0134] It can be seen from the data in Table 1 and Table 2 that the method of the present invention can improve the residual strength of lithium aluminum silicate glass after damage, is simple to operate, and significantly improves the strength.
[0135] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for improving the residual strength of lithium aluminum silicate glass after damage, characterized in that: The method comprises the following steps: The lithium aluminosilicate glass with surface damage is subjected to a first preheating treatment, a first molten salt strengthening treatment, a first annealing treatment, a second preheating treatment, a second molten salt strengthening treatment, a second annealing treatment, a first heat treatment, a third preheating treatment, a third molten salt strengthening treatment, a third annealing treatment, a hot and cold shock treatment, a second heat treatment, and a corrosion treatment in sequence to obtain a target lithium aluminosilicate glass; the thickness of the lithium aluminosilicate glass is 2 mm to 10 mm.
2. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The damage depth of the surface damage is ≤0.5mm and not 0; Preferably, the surface damage includes at least one of scratches, erosion and bumps.
3. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The first preheating treatment, the second preheating treatment and the third preheating treatment each independently include: The lithium aluminum silicate glass is heated from room temperature to 340° C. to 380° C. at a heating rate of 1° C. / min to 3° C. / min, and kept at this temperature for 1 h to 3 h.
4. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The temperature of the first molten salt strengthening treatment is 380° C. to 450° C., and the time is 3 h to 24 h; and / or, The temperature of the second molten salt strengthening treatment is 380° C. to 450° C., and the time is 0.5 h to 5 h; and / or, The temperature of the third molten salt strengthening treatment is 380° C. to 450° C., and the time is 0.5 h to 3 h.
5. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1 or 4, characterized in that: The first molten salt strengthening treatment, the second molten salt strengthening treatment and the third molten salt strengthening treatment each independently use a mixed molten salt containing potassium nitrate, sodium nitrate and calcium fluoride, and the mass percentage of potassium nitrate and sodium nitrate in the mixed molten salt used in the first molten salt strengthening treatment is different from the mass percentage of potassium nitrate and sodium nitrate in the mixed molten salt used in the second molten salt strengthening treatment and the third molten salt strengthening treatment.
6. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 5, characterized in that: In the mixed molten salt used in the first molten salt strengthening treatment, the mass percentage of the sodium nitrate is 65% to 85%, the mass percentage of the calcium fluoride is 0.5%, and the balance is sodium nitrate; Preferably, in the mixed molten salt used in the second molten salt strengthening treatment and the third molten salt strengthening treatment, the mass percentage of potassium nitrate is 80% to 90%, the mass percentage of calcium fluoride is 0.5%, and the balance is sodium nitrate.
7. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The first annealing treatment, the second annealing treatment and the third annealing treatment each independently include: The lithium aluminum silicate glass after molten salt strengthening treatment is cooled to room temperature at a cooling rate of 1° C. / min to 3° C. / min.
8. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The first heat treatment comprises: in a vacuum or oxygen atmosphere, heating the lithium aluminum silicate glass from room temperature to 380° C. to 450° C. at a heating rate of 1° C. / min to 3° C. / min, and keeping the temperature for 2 h to 4 h; Preferably, the second heat treatment comprises: in vacuum or oxygen atmosphere, heating the lithium aluminum silicate glass from room temperature to 80°C to 100°C at a heating rate of 1°C / min to 3°C / min, and keeping the temperature for 96h to 120h.
9. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The thermal shock treatment comprises: subjecting the lithium aluminum silicate glass to thermal shocks for 5 to 10 times, each thermal shock temperature being 70° C. and each cold shock temperature being −40° C.
10. The method for improving the residual strength of lithium aluminosilicate glass after damage according to claim 1, characterized in that: The corrosion treatment comprises: performing corrosion treatment on the damaged surface of the lithium aluminum silicate glass for a corrosion time of 1 to 2 minutes; Preferably, the etching solution used in the etching treatment contains potassium hydroxide.